Analisis Faktor-Faktor Penyebab Kesulitan Belajar Bahasa Arab Pada Mahasiswa Alumni Sekolah Umum - Farihana, Intan Rahmadany; Mufidah, Nuril (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2024)
This study aims to analyze the factors that make it difficult for students of the Arabic language education program, and alumni of public schools, to learn Arabic. In this study using qualitative research methods. The author's analysis of the general school alumni students of the Arabic Language Education Study Program found that there were various types of difficulties, as well as several factors experienced when learning Arabic. This type of difficulty can be caused by various factors, both internal factors (inside a student) and external factors (coming from the environment). Internal factors that influence student academic success (these factors include two aspects) are physical factors (such as physical health) and psychological factors (such as spiritual well-being). And caused by factors that come from outside a student. There are three types of environments: family, school, and community. The factors of difficulty in learning Arabic faced by graduates of public schools of the Arabic Language Teaching Study Program, namely: curriculum factors, student factors, educator factors, method factors, media factors, facilities factors, social or environmental factors, physiological factors, and psychological factors . Strategies that can be used by lecturers to help students who have difficulties include providing Arabic tutoring, trying to attract students' interest in learning Arabic, giving all forms of attention, and providing various infrastructure facilities that are considered adequate. Penelitian ini bertujuan untuk menganalisis faktor-faktor yang menyulitkan mahasiswa program pendidikan bahasa Arab alumni sekolah umum untuk belajar bahasa Arab. Dalam penelitian ini menggunakan metode penelitian kualitatif. Analisis penulis terhadap mahasiswa alumni sekolah umum Prodi Pendidikan Bahasa Arab menemukan bahwa ada berbagai jenis kesulitan, juga beberapa faktor yang dialami ketika belajar bahasa Arab. Jenis kesulitan tersebut dapat disebabkan karena berbagai faktor, baik faktor dari dalam (dalam diri seorang siswa) dan faktor dari luar (berasal dari lingkungan). Faktor dari dalam yang mempengaruhi keberhasilan akademik mahasiswa (faktor tersebut meliputi dua aspek) yaitu faktor fisik (seperti kesehatan fisik) dan faktor psikologis (seperti kesejahteraan spiritual). Dan disebabkan karena faktor yang berasal dari luar diri seorang siswa. Ada tiga jenis lingkungan : dari keluarga, sekolah, dan masyarakat. Faktor-faktor kesulitan belajar bahasa Arab yang dihadapi lulusan sekolah umum Program Studi Pengajaran Bahasa Arab, yaitu: faktor kurikulum, faktor peserta didik, faktor pendidik, faktor metode, faktor media, faktor fasilitas, faktor sosial atau lingkungan, faktor fisiologis, dan faktor psikologis. Strategi yang dapat digunakan dosen untuk membantu siswa yang kesulitan diantaranya dengan memberikan bimbingan belajar bahasa Arab, berusaha menarik minat para mahasiswa dalam belajar bahasa Arab, memberikan segala bentuk perhatian, dan menyediakan berbagai sarana prasarana yang dianggap cukup memadai.